Connector sets and interconnect components to be used in optical fibre communication systems. Product specifications. Type 4+4x10.3125 Gb/s MPO (QFSP) transceiver mated with an MPO connector equipped with 12 fibre PPS ferrules terminated on EN 60793-2-10 category A1a.3a or A1a.3b 50/125 micron multimode fibre Part 18-1, (2nd May 2019) - British Standards Institution
No abstract available